The neuroblastoma associated F1174L ALK mutation causes resistance to an ALK kinase inhibitor in ALK translocated cancers - Sasaki, Takaaki (2010)
The ALK kinase inhibitor crizotinib (PF-02341066) is clinically effective in patients with ALK-translocated cancers, but its efficacy will ultimately be limited by acquired drug resistance. Here we report the identification of a secondary mutation in ALK, F1174L, as one cause of crizotinib resistance in a patient with an inflammatory myofibroblastic tumor (IMT) harbouring a RANBP2-ALK translocation who progressed while crizotinib therapy. When present in cis with an ALK translocation, this mutation (also detected in neuroblastomas) causes an increase in ALK phosphorylation, cell growth and downstream signaling. Furthermore, the F1174L mutation inhibits crizotinib mediated downregulation of ALK signaling and blocks apoptosis in RANBP2-ALK Ba/F3 cells. A chemically distinct ALK inhibitor, TAE684, or the HSP90 inhibitor 17-AAG are both effective in models harbouring the F1174L ALK mutation. Our findings highlight the importance of studying drug resistance mechanisms in order to develop effective clinical treatments for patients with ALK-translocated cancers.